Risk Potential of Pipeline Gas Leaks in Dhaka City: Causes, Cfonsequenses and Mitigation Strategies (Chemical Engineering Research Bulletin, 2023)
Gas transmission lines are some of the most essential parts of the infrastructure of an area as it plays an indispensable role in fulfilling the need for energy in households, shops, plants, and industries. In densely populated areas, such as Dhaka, Bangladesh, however, the possibility of gas ejection from these transmission lines is a major concern. This paper seeks to investigate the potential impact of gas pipelines leaks in Dhaka city, identify its causes, and suggest preventive measures. The study begins with a review of the existing research on gas pipeline leaks, focusing on their catastrophic effects on lives, households, and communities. Identification of the alarming increase in gas leakage incidents by analysing historical data and incident reports and highlighting the imperative need for preventative measures is the next step. The findings highlight the vulnerability of densely populated areas and the catastrophic effects of gas pipeline failures. A conclusion is supported with a variety of preventative measures and risk mitigation strategies to reduce the frequency and severity of gas leakage incidents in Dhaka city by implementing these strategies. This paper contributes to the field by increasing awareness of the rising risk of gas pipelines leakage and its potential effects on densely populated areas like Old Dhaka. The proposed preventive measures serve as the basis for policymakers, gas companies, and other relevant stakeholders to develop comprehensive strategies to ensure the safety and well-being of the community.Chemical Engineering Research Bulletin 23 (2023): 84-88